Effects of a radial variation of surface coefficients on plasma uniformity in capacitive RF discharges. (1st April 2023) - Wang, Li; Hartmann, Peter; Donkó, Zoltán; Song, Yuan-Hong; Schulze, Julian
Abstract: With the increasing demands toward large area plasma etching and deposition, the radial uniformity of capacitively coupled plasmas (CCPs) becomes one of the key factors that determine process performance in industrial applications. However, there is a variety of parasitic effects, e.g. electromagnetic and electrostatic edge effects, that typically lead to the formation of nonuniform radial plasma density profiles at various discharge conditions with a density peak appearing either at the center or near the edges of the electrodes. Moreover, in commercial CCPs different surface materials are in contact with the plasma at various positions as parts of boundary surfaces such as focus rings, masks, showerhead electrodes, wall and/or target materials. Via complex material specific plasma-surface interactions, the presence of such different surface materials affects plasma uniformity in a way that is typically not understood and, thus, not controlled. In this work, aided by 2d3v graphics processing unit accelerated particle-in-cell/Monte Carlo collision simulations, we study the effects of radial variations of electrode materials on the plasma via their different ion and electron induced secondary electron emission as well as electron reflection coefficients on the discharge characteristics. Based on such fundamental understanding we tailor the radial variation of boundary surface materials to improve plasma uniformity in low pressure CCPs. Such investigations are performed at different neutral gas pressures, where both center and edge high radial plasma density profiles form in the presence of radially uniform surface coefficients that resemble the presence of a single electrode material. It is demonstrated that by radially varying the surface coefficients at the grounded electrode, the radial plasma density profile can be finely adjusted and the plasma uniformity above the wafer placed at the powered electrode can be improved in both cases.